Local Content Integration Model and the Value of Science Characters in Students Junior High School In Banda Aceh - Ibrahim Ibrahim; Nurul Akmal; Almukarramah Almukarramah; Marwan Marwan; Yahya Don; Mohd Isha Awang (JURNAL SERAMBI ILMU, 2022)
In implementing the teaching and learning process with Islamic characters in junior high schools, it is carried out based on the 2013 character curriculum. In the teaching materials, teachers must be able to relate the pattern of human life to socio-cultural values, religion and ways of interaction in Islamic Acehnese society. This study aims to know how patterns and ways to integrate science values with character and how students' attitudes change after the learning process at SMP Negeri Banda Aceh. The population in this study were all public junior high school students in five regions in Aceh whose character represented the area. The sample consisted of 102 third grade students who were taken randomly.They follow the learning process by integrating character values in three meetings with teaching materials on ecosystems and the interaction of living things with the environment which ends with a post test to get the value of student learning outcomes. The data processing method uses t-test statistics. the results of the study showed that there was an increase in student achievement after using the integration model in learning with ecosystem and environmental teaching materials. We also believe that the model of integrating local wisdom values is able to shape the character of students, so it needs support from all parties for implementation in the field.